A mechanism-based gradient damage model for metallic fracture. (1st October 2021) - Shishvan, Siamak S.; Assadpour-asl, Saeid; Martínez-Pañeda, Emilio
Highlights: A new mechanism-based model for predicting fracture in elastic–plastic solids is presented. We combine phase field with a gradient plasticity theory based on Taylor's dislocation model Finite element analysis is conducted to understand the interplay between fracture and plasticity length scales When defects are sharp, plastic strain gradients elevate local stresses and facilitate fracture. In the presence of non-sharp defects, plastic strain gradients delay plastic flow localisation and failure. Abstract: A new gradient-based formulation for predicting fracture in elastic–plastic solids is presented. Damage is captured by means of a phase field model that considers both the elastic and plastic works as driving forces for fracture. Material deformation is characterised by a mechanism-based strain gradient constitutive model. This non-local plastic-damage formulation is numerically implemented and used to simulate fracture in several paradigmatic boundary value problems. The case studies aim at shedding light into the role of the plastic and fracture length scales. It is found that the role of plastic strain gradients is twofold. When dealing with sharp defects like cracks, plastic strain gradients elevate local stresses and facilitate fracture. However, in the presence of non-sharp defects failure is driven by the localisation of plastic flow, which is delayed due to the additional work hardening introduced by plastic strain gradients.